1994
DOI: 10.1288/00005537-199410000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Immune‐mediated inner ear disease and parvovirus b19

Abstract: Human parvovirus B19 (HP-B19), the etiologic agent of the common childhood illness erythema infectiosum, has been implicated in systemic immune disorders. Patients presenting with sensorineural hearing loss and/or dizziness, not readily categorized, were evaluated for immune-mediated inner ear disease. Appropriate serologic studies including parvovirus B19 antibody titers were conducted. Thirty patients with suspected immune-mediated inner ear disease were treated with corticosteroid trial for 5 to 7 days, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…In adults, HPV-B19 causes a variety of clinical manifestations, although about 75% of infected individuals have non-specific flu-like symptoms or are completely asymptomatic (Woolf et al 1989;Hayakawa et al 2002). For HPV-B19 infection, however, since there has been only one report about inner ear symptoms (Cotter et al 1994), our patient may represent a rare case given the hearing difficulty and dizziness. In the present patient, hearing levels were within normal limits by pure-tone audiometry.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…In adults, HPV-B19 causes a variety of clinical manifestations, although about 75% of infected individuals have non-specific flu-like symptoms or are completely asymptomatic (Woolf et al 1989;Hayakawa et al 2002). For HPV-B19 infection, however, since there has been only one report about inner ear symptoms (Cotter et al 1994), our patient may represent a rare case given the hearing difficulty and dizziness. In the present patient, hearing levels were within normal limits by pure-tone audiometry.…”
Section: Discussionmentioning
confidence: 83%
“…However, ear symptoms (hearing difficulty and dizziness) are not usually categorized as HPV-B19 associated symptoms. Concerning the ear symptoms of HPV-B19 infection, to our knowledge there has been only one report (Cotter et al 1994).…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Failure to detect HSV, varicella zoster virus (VZV) and cytomegalovirus (CMV) in the vestibular ganglion of Ménière's disease could not rule out a potential viral etiology of Mé-nière's disease, because vestibular ganglion cells are not the pathological site of the disease [7] . It has been reported that some viruses have the ability to modulate the immune system and induce autoimmune inner ear disease and change the patient's response to corticosteroids [8] . Recently, experimental models have been developed to investigate how some viral infections can prime for, and trigger, autoimmune responses, whereas others ameliorate the pathway leading to clinical disease [9,10] .…”
Section: Introductionmentioning
confidence: 99%